2007
DOI: 10.1177/0022343307080855
|View full text |Cite
|
Sign up to set email alerts
|

www.PeaceTest.org: Development, Implementation, and Evaluation of a Web-Based War-Prevention Program in a Time of War

Abstract: Collective violence is a major cause of death, illness, and suffering. The theory of moral disengagement offers a framework for understanding and preventing violence between nations, and the Internet provides a vehicle for reaching a diverse population with a war-prevention program. The objectives of the PeaceTest project were to develop, implement, and evaluate a theory-based interactive website to be used as a war-prevention intervention for a general audience. The open-access site www.PeaceTest.org is an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Unlike the conclusions drawn from several other investigations (Bandura et al, 1996;Howard et al, 2007;Jackson & Sparr, 2005;McAlister et al, 2006), in the present study men and participants with a lower educational level did not demonstrate more moral disengagement than women and participants with a higher education level. In contrast, an attitude of moral disengagement manifested less often in the comments of people with a lower level of education (Alejandra, Sofi, John, Max y Gerónimo).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the conclusions drawn from several other investigations (Bandura et al, 1996;Howard et al, 2007;Jackson & Sparr, 2005;McAlister et al, 2006), in the present study men and participants with a lower educational level did not demonstrate more moral disengagement than women and participants with a higher education level. In contrast, an attitude of moral disengagement manifested less often in the comments of people with a lower level of education (Alejandra, Sofi, John, Max y Gerónimo).…”
Section: Discussioncontrasting
confidence: 99%
“…Only one recent study explores the use of moral disengagement in the context of Colombian armed conflict but in the communiqués of FARC and a paramilitary group (AUC, in its Spanish acronym), not in the general population (Villegas, Flórez, & Espinel, 2018). Second, some international studies suggest that women (Bandura et al, 1996;Howard, Shegog, Grussendorf, Stelzig, & McAlister, 2007;McAlister et al, 2006) and people with a higher level of education (Jackson & Sparr, 2005;McAlister et al, 2006) are more resistant to moral disengagement. Additionally, the mechanism of dehumanization has been associated with an increase in the perception of threat and an increase in discrimination against the victim (Demoulin, Rodríguez et al, 2004;Pereira, Vala, & Leyends, 2009 as cited in Piñuela, 2014), as well as with opposition to reparation policies amid political conflicts (Zebel, Zimmerman, Tendayi Viki, & Doosje, 2008).…”
Section: Moral Disengagementmentioning
confidence: 99%
“…Another example of an educational intervention aimed at reducing MD is the PeaceTest project (Howard et al, 2007). This project involved a theory-based MD interactive website designed to be a war-prevention intervention for a general audience.…”
Section: Discussionmentioning
confidence: 99%
“…Martín-Peñ a and Opotow (2011) described how the ETA (a terrorist separatist group in Spain) has used tactics such as euphemisms, displacement of responsibility and blaming the victim in narratives designed to justify their violence. Although the evidence is mixed, the bulk of the relevant studies found that in comparison to men, women were significantly less morally disengaged (Ashy and Malley-Morrison, 2007;Caprara et al, 2009;Grussendorf et al, 2002;Hashim and Malley-Morrison, 2007;Howard et al, 2007;Mcalister et al, 2006). Moreover, there is some evidence that women are significantly more morally engaged than men in regards to government aggression (Malley-Morrison et al, 2009).…”
Section: The Gender Gapmentioning
confidence: 99%
“…5702 (76%) completed the pre-test, and 338 (6%) of these completed the post-test. Seventy-five per cent recorded peace test scores indicating they were at risk of moral disengagement while those who completed reviewing material and took the post-test showed an increase in resistance to moral disengagement (Howard et al 2007). McAlister et al studied levels of moral disengagement in children aged 13-18 in Estonia, Finland, Romania, the Russian Federation and the US.…”
mentioning
confidence: 99%